2016
DOI: 10.1080/02699052.2016.1186840
|View full text |Cite
|
Sign up to set email alerts
|

Co-morbid conditions in use of recombinant tissue plasminogen activator (rt-PA) for the treatment of acute ischaemic stroke

Abstract: The findings indicate that certain risk factors including carotid stenosis, CHF and previous stroke history impact the treatment of patients with acute ischaemic stroke, specifically the decision to administer rt-PA. Treatment with rt-PA is dependent on stroke severity and onset to treatment time, but the findings suggest that rt-PA use may also depend on patient comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 41 publications
3
26
0
Order By: Relevance
“…It has been shown that specific comorbidities may influence the benefits of thrombolytic therapy in patients with ischemic stroke. [19][20][21][22][23][24][25] In addition, we know that some risk factors for TIA and ischemic stroke including hypertension (HTN), diabetes, and heart diseases 20,[25][26][27][28][29][30][31] may interact with thrombolytic therapy to significantly modulate ambulation and affect treatment outcome. In this case, one possibility is that perhaps specific clinical risk factors in patients with TIA-ischemic stroke may increase the odds of good or poor functional ambulation outcome because of the resulting interactive effect with thrombolytic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that specific comorbidities may influence the benefits of thrombolytic therapy in patients with ischemic stroke. [19][20][21][22][23][24][25] In addition, we know that some risk factors for TIA and ischemic stroke including hypertension (HTN), diabetes, and heart diseases 20,[25][26][27][28][29][30][31] may interact with thrombolytic therapy to significantly modulate ambulation and affect treatment outcome. In this case, one possibility is that perhaps specific clinical risk factors in patients with TIA-ischemic stroke may increase the odds of good or poor functional ambulation outcome because of the resulting interactive effect with thrombolytic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Previous TIA is not a formal contraindication for rtPA, especially if the TIA was at least three months before the onset of stroke [28] [22,29]. However, it has been shown that the onset of TIA within 24 hours of stroke may lead to a poor outcome following rtPA [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Data within the Greenville Health System (GHS) stroke registry has been standardized according to the "Get with The Guidelines" (GWTG) stroke registry formed by the American Heart Association (AHA). Details in the ascertainment and data collection have previously been described [22][23][24]. Briefly, data was collected from 1466 ischemic stroke patients admitted to the stroke Unit of GHS between January 2014 and June 2016 with a diagnosis of acute ischemic stroke.…”
Section: Methodsmentioning
confidence: 99%
“…Data within the Greenville Health System (GHS) stroke registry has been standardized according to the "Get with The Guidelines" (GWTG) stroke registry formed by the American Heart Association (AHA). Details in the ascertainment and data collection have previously been described [22][23][24] Clinical parameters relating to the hospital course included data of stroke patients in the use of rtPA for the 4.5 hours of the protocol. We included data on laboratory analyses of samples including serum lipid panel, LDL, total cholesterol and creatinine levels.…”
Section: Methodsmentioning
confidence: 99%